Evaluating the Impact of Local Vaccine Manufacturing on the Resilience and Responsiveness of the Vaccine Supply Chain: A Case Study within South Africa - Obermeyer, Heino Stewart (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.